2017
DOI: 10.1142/s0218810417500290
|View full text |Cite
|
Sign up to set email alerts
|

Thumb Function and Electromyography Result after Modified Camitz Tendon Transfer

Abstract: Background: Various techniques of opponensplasty have been developed with the aim of restoring the thumb function. The modified Camitz opponensplasty is a simple technique done together with an open carpal tunnel release. It restores thumb palmar abduction soon after the procedure, during such time that the abductor pollicis brevis (APB) is still recovering. The aim of this study was to assess the recovery and level of activity of the abductor pollicis brevis and palmaris longus (PL) muscles during thumb oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…We believe that measuring thumb pronation angle using a gyroscope has many advantages. Kapandji scores [ 44 ] are widely used to evaluate thumb opposition in clinical practice [ 20 , 45 52 ]. However, it is not an accurate quantitative evaluation method but only a numerical categorized method; moreover, there were reports that almost all healthy subject and even CTS patients with thenar atrophy were able to obtain 9 or 10 points of this score [ 22 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that measuring thumb pronation angle using a gyroscope has many advantages. Kapandji scores [ 44 ] are widely used to evaluate thumb opposition in clinical practice [ 20 , 45 52 ]. However, it is not an accurate quantitative evaluation method but only a numerical categorized method; moreover, there were reports that almost all healthy subject and even CTS patients with thenar atrophy were able to obtain 9 or 10 points of this score [ 22 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The control group underwent standard surgical decompression, and the intervention group underwent surgical decompression with a single injection of platelet-rich plasma introduced through the mini-vacuum drain [31]. Similarly, modified Camitz opponensplasty did not correlate with neurologic and muscle recovery in a study of 21 participants with severe CTS [32]. A retrospective study that compared endoscopic carpal tunnel release with open carpal tunnel release did not find any differences in outcomes, including electromyographic abnormalities [33].…”
Section: Discussionmentioning
confidence: 95%
“…Even in individuals with missing motor nerve function on preoperative nerve conduction testing, Park et al[ 29 ] found that thenar atrophy could improve concurrently with motor recovery after CTR alone. According to Durban et al[ 30 ] and Hattori et al,[ 31 ] more than one-third of patients with severe CTS and thenar atrophy showed electrophysiological recovery of APB during the postoperative period. In our study, in three hands in contractile group, thenar atrophy recovered, while non-stimulated group showed no recovery.…”
Section: Discussionmentioning
confidence: 99%